Multimedia forage farmer training modules: Grass 2 Cash @Scale Project - Kagendo, Sophia; Jeptoo, Mercy; Valeton, Alexander; Odhiambo, Ruth; Muthomi, Fredrick; Misoi, Solomon; Mugo, Peggy; Sibiko, Kenneth; Hansen, Andreas; Ohmstedt, Uwe; Jansen, Anton; Mwangi, David Miano; et al. (2023)
This manual provides comprehensive farmer training modules that cover various aspects of forage production. Topics include the rationale for forage production (with potential business models), the entire production process from land preparation, forage establishment, management, harvesting, to conservation. Additionally, it offers guidelines on proper livestock feeding to achieve optimal production potential. The training guide is presented in a multimedia format, featuring engaging pictorial illustrations and links to informative Shamba Shapeup YouTube videos that detail the processes involved. It is well-structured, with clear learning objectives at the beginning and quizzes at the end of each module to assess understanding. This resource is valuable for training facilitators, agriculture students, farmers, researchers, and agricultural extension providers.